How Organizational Commitment Mediates Teacher Competence and Work Discipline on Student Learning Outcomes - Risma Wahyuni; Djoko Soelistya (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
In the context of education, the achievement of learning outcomes has an important role as an indicator of the effectiveness of the learning process. This study aims to examine the role of organizational commitment as a mediating factor in the influence of teacher competence and work ethic on learning outcomes. This study involved 31 instructors as the study population and used a quantitative approach with the SmartPLS 3.0 analysis tool. The research findings show that: (1) teacher competence has no significant effect on learning outcomes, (2) teacher competence has a significant effect on organizational commitment, (3) work discipline has no significant effect on organizational commitment, (4) work discipline has an influence significant effect on organizational commitment, (5) organizational commitment has a significant impact on learning outcomes, and (6) teacher competence directly influences learning outcomes through work discipline factors and organizational commitment which are closely interrelated.